A comparison of mental state examination documentation by junior clinicians in electronic health records before and after the introduction of a semi-structured assessment template (OPCRIT+). Issue 9 (September 2015) - Lobo, Sarah E.M.; Rucker, James; Kerr, Madeleine; Gallo, Fidel; Constable, Giles; Hotopf, Matthew; Stewart, Robert; Broadbent, Matthew; Baggaley, Martin; Lovestone, Simon; McGuffin, Peter; Amarasinghe, Myanthi; et al.
Highlights Junior psychiatrists notes were compared before and after the use of a template. Template notes were rated as more thorough, organized, useful and comprehensible. An audit revealed template notes contained more clinically relevant information.